(untitled) (Per Musi, 2011)
This paper intends to point out contextual and musical elements, especially those relative to expressiveness, that brings Wilhelm Friedemann Bach’s keyboard works close to German Sturm und Drang, that happened during the beginning of the second half of the eighteenth century, through the identification of the literary and musical procedures and the analysis of the Polonaise number 4, in D minor, as a representative work of this style.